TEACHER’S PERCEPTION OF THE IMPLEMENTATION OF HIGHER ORDER THINKING SKILLS (HOTS) IN ELT PROCESS - Bulkis, Iin; Abduh, Amirullah; Sakkir, Geminastiti (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study aimed to determine the implementation of HOTS in the ELT process in the 8th grade of UPT SPF SMPN 27 Makassar and to determine the perception of the 8th grade English teacher of UPT SPF SMPN 27 Makassar regarding the implementation of HOTS in the ELT process. The researchers applied a qualitative descriptive method. The research data were collected through observation, interviews, and documentation. The subjects of this study were two English teachers who teach in grade 8 of UPT SPF SMPN 27 Makassar. The results of data analysis found that (1) the implementation of HOTS in grade 8 of UPT SPF SMPN 27 Makassar has been implemented very well by the teacher in the classroom (2) the teacher's perception of HOTS is positive based on the implementation, language development, and student enthusiasm.